Translational queer fandom under “han-xu” politics in China: A case study of the Wanwan subtitling group - Song, Qijun (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2024)
Building on previous studies about “non-confrontational” activism among Chinese queer translation groups, this article explores the subtitling and social media practices of Wanwan, a Chinese lesbian-oriented fansubbing group, from a cultural–ideological perspective. It argues that Wanwan’s practices can be better understood in the context of han-xu (??, reticent) politics, shaping a non-confrontational activist approach to fansubbing. This approach is manifested through diversified content that involves both queer and non-queer media resources, recontextualised translated subtitles, the creation of spaces for interactions, and the production of reflexive paratexts that refrain from overt criticism of cis-heteronormativity. The article contributes to an understanding of translational queer fandom in China by arguing that groups such as Wanwan not only foster a dedicated fan community and a “by queers for queers” world, but also bridge the communication gap between queer communities and cis-heteronormative groups without exacerbating the cultural and ideological tensions that might otherwise set them apart.